BAGAIMANA CASH FLOW SHENANIGANS DAPAT MENGINDIKASI MANIPULASI KEUANGAN PADA PT KRAKATAU STEEL? - Khairani, Dian; Hijriah, Amanah; Desyana, Gita (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2025)
This research is motivated by findings of financial statement manipulation, including at PT Krakatau Steel, which was involved in a corruption scandal. Financial statement manipulation can occur in various forms, one common type being the manipulation of cash flow statements, or cash flow shenanigans, with the aim of misrepresenting a company's cash flow. This study aims to analyze the cash flow statements of PT Krakatau Steel to identify indications of financial manipulation. The research method used is qualitative with content analysis techniques, using secondary data from the cash flow and income statements of PT Krakatau Steel from 2011 to 2015. The analysis results indicate that there are indications of manipulation in the cash flow statements of PT Krakatau Steel through two cash flow shenanigans techniques: recording cash flow from loans as false operating cash flow, and recording receipts from the sale of fixed assets that do not match other income in the income statement.